Surveying the selection landscape: A systematic review of processes for selecting postgraduate year 1 pharmacy residents and key implications. Issue 2 (12th October 2020) - Reed, Brent N.; Noel, Zachary R.; Heil, Emily L.; Shipper, Andrea G.; Gardner, Aimee K.
Abstract: Introduction: The growth in applicants to postgraduate year one (PGY1) pharmacy residency programs outpaces the number of available positions, requiring that residency program directors (RPDs) evaluate an increasing number of qualified candidates. Discrepancies exist in the characteristics thought to distinguish exemplary candidates and the methods for selecting them. Objectives: To characterize the burdens of the selection process, summarize methods for selecting PGY1 residents based on a systematic review, and list best practices for improving the process. Methods: Burdens were characterized by collecting applicant costs via survey and program costs and workload estimates via interviews of RPDs at small, medium, and large programs. For the systematic review, a medical librarian searched for articles pertaining to resident selection. Articles underwent a title/abstract screen and full text screen by two authors and a third served as tiebreaker. Data were summarized in descriptive form, and consisted of study methodology, selection method(s) of interest, and principal findings. Results: The median cost to applicants was $1756 (interquartile range [IQR] $1271‐$2423). The median cost to residency programs was $5068 (IQR $3943‐$12 310). Program directors spent a median of 56.5 hours on selection; a median of 22.0 and 21.3 hours were spent by each preceptor and current resident, respectively. A total of 51 articles (22 surveys and 29 other designs) were included in the systematic review. Biographical data, interviews, and references were among the most commonly explored evaluation methods. Articles consisted primarily of descriptions of selection methods, summaries of RPD attitudes regarding these methods or characteristics desired in a resident, or factors that predicted a successful match. Few articles investigated the validity and reliability of selection methods. Conclusion: Selection is a cumbersome process for both applicants and programs alike. Fortunately, numerous opportunities exist to improve the process, and these should serve as the basis of future research.